2017
DOI: 10.1007/s12630-017-0989-7
|View full text |Cite
|
Sign up to set email alerts
|

Effect of dexamethasone dose and route on the duration of interscalene brachial plexus block for outpatient arthroscopic shoulder surgery: a randomized controlled trial

Abstract: www.clinicaltrials.gov (NCT02426736). Registered 14 April 2015.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
46
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 47 publications
(49 citation statements)
references
References 30 publications
2
46
1
Order By: Relevance
“…For interscalene blocks, studies by Tandoc et al ,2 Woo et al ,26 and Holland et al 27 have found no intergroup differences in terms of block duration or time to first analgesia. In contrast, for supraclavicular blocks, Patel et al 28 detected longer motor blockade and postoperative analgesia with 8 mg compared with 4 mg of PN dexamethasone.…”
Section: Discussionmentioning
confidence: 94%
See 1 more Smart Citation
“…For interscalene blocks, studies by Tandoc et al ,2 Woo et al ,26 and Holland et al 27 have found no intergroup differences in terms of block duration or time to first analgesia. In contrast, for supraclavicular blocks, Patel et al 28 detected longer motor blockade and postoperative analgesia with 8 mg compared with 4 mg of PN dexamethasone.…”
Section: Discussionmentioning
confidence: 94%
“…In light of the conflicting results stemming from previous studies by Tandoc et al ,2 Woo et al ,26 Holland et al ,27 and Patel et al ,28 a practical argument could be made to systematically administer 8 mg of PN dexamethasone for brachial plexus blocks, thereby increasing the odds of maximizing postoperative analgesia. However, despite its increasing popularity,1–21 PN remains an off-label adjuvant.…”
Section: Discussionmentioning
confidence: 99%
“…Albrecht et al (2015), in their meta-analysis, concluded that perineural dexamethasone was associated with longer duration of analgesia and can reduce postoperative morphine consumption and pain scores (Albrecht et al, 2015). Holland and his colleagues also found that perineural dexamethasone increases the duration of interscalene block despite the dose and the administration route (Holland et al, 2018).…”
Section: Discussionmentioning
confidence: 99%
“…Limited comparative efficacy among routes of administration has emerged. This appears most true for dexamethasone, which confers similar benefits to pain control and opioid use when administered via either modality [259,[327][328][329][330]333]. Although administering dexamethasone as a component of peripheral nerve blockade may avoid systemic side effects, perineural dexamethasone may have a local effect on nerve tissues that may be undesirable in some patient populations.…”
Section: Systemic Multimodal Adjunctsmentioning
confidence: 99%